Enhancing Parents’ Engagement for Quality Children Education Through Smart Application of Parenting - Syahrir, Muhammad; Sepatriani, Sella Fadia; Alam, Naufal Ahmad Rijalul (Universitas Muhammadiyah Yogyakarta, 2021)
This article aims to develop innovations in the form of education applications, parenting and help parents understand the correct concept in providing education to children. The methodology of this research uses a qualitative approach whose samples are parents as the main actors in the role of the family. Data collection techniques used are questionnaires and interviews. By doing research, it can be concluded that there is a need for an application that can help parents in implementing good and quality parenting by utilizing technology in the form of smart application innovations.